2019
DOI: 10.1186/s13068-019-1567-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective editing for lysophosphatidic acid acyltransferase 2/5 in allotetraploid rapeseed (Brassica napus L.) using CRISPR-Cas9 system

Abstract: Background Brassica napus is one of the most important oilseed crops, and can supply considerable amounts of edible oil as well as provide raw materials for the production of biodiesel in the biotechnology industry. Lysophosphatidic acid acyltransferase (LPAT), a key enzyme in the Kennedy pathway, catalyses fatty acid chains into 3-phosphoglycerate and promotes further production of oil in the form of triacylglycerol. However, because B. napus is an allotetraploid with two subgenomes, the preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 63 publications
4
41
0
Order By: Relevance
“…In less than two years, stably inheriting homozygous T 3 winter‐type mutant lines could be selected. As shown in previous studies (Yang et al , 2018; Zhang et al , 2019), we also found T 1 plants with more than two alleles (haplotypes) at one locus as clear evidence for chimerism. A possible explanation is the low activity of the Cas9 nuclease caused by partial transgene silencing in the BnSFAR5 T 1 plant, which carries multiple transgene insertions.…”
Section: Discussionsupporting
confidence: 90%
“…In less than two years, stably inheriting homozygous T 3 winter‐type mutant lines could be selected. As shown in previous studies (Yang et al , 2018; Zhang et al , 2019), we also found T 1 plants with more than two alleles (haplotypes) at one locus as clear evidence for chimerism. A possible explanation is the low activity of the Cas9 nuclease caused by partial transgene silencing in the BnSFAR5 T 1 plant, which carries multiple transgene insertions.…”
Section: Discussionsupporting
confidence: 90%
“…Grains with high amylose content and resistant starch has human health benefits. CRISPR/Cas9 genome editing shows that knockout of pat2/5 genes resulted in increased accumulation of starch in the mature seeds of allotetraploid rapeseed [124] . Sun and colleagues (2018) employed CRISPR/Cas technology to successfully knockout the starch branching enzyme (SBE) gene SBEIIb and generated genome-edited rice with high content of amylose, in which up to 25% of amylose was generated with higher proportion of long chain in debranched amylopectin in rice seeds [125] .…”
Section: Application Of Crispr/cas On Crop Improvementmentioning
confidence: 99%
“…By overexpressing the fatty acid elongase gene ( fae1 ) simultaneously with the lysophosphatidic acid acyltransferase gene from Limnanthes douglasii (Ld-LPAAT), erucic acid synthesis was predominant over PUFA synthesis in competitive elongation to the triaclyglycerol backbone in transgenic lines, which resulted in an increase in erucic acid content of up to 72% and a PUFA content as low as 6% [ 13 ]. The roles of LPAAT genes of B. napus , BnLPAT2 and BnLPAT5, in regulating oil biosynthesis has been recently confirmed by targeted mutations using Cas9 with single-gRNAs and multi-sgRNAs whereby the resulted Bnlat2 and Bnlat5 mutants showed decreased oil content and enlarged oil bodies [ 33 ]. Cytoplasmic genomes are also attracting more interest as the new approach for maximizing oil content in canola [ 90 ].…”
Section: Breeding For Economically Important Agronomic Traits Ofmentioning
confidence: 99%
“…Limitations in gene pool diversity [ 31 , 32 ], and the time and laborious constraints in canola breeding can now be overcome by using genetic modification [ 32 ] and genome editing technologies whereby transgenes or mutations can be directly introduced into plants, providing additional ways to investigate gene functions in biological processes [ 33 , 34 , 35 , 36 ]. The most commonly applied genome editing tool in eukaryotes in the last 8 years, the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein (Cas) system [ 37 , 38 ], is gaining more interest compared to conventional genetic modification methods due to its high efficiency in targeted nucleotide modification and generation of a transgene-free end-product [ 39 ].…”
Section: Introductionmentioning
confidence: 99%